Electricity and Firm Productivity: A General-Equilibrium Approach - Stephie Fried; David Lagakos (Center for Economic Studies and ifo Institute (CESifo), 2021)
Many policymakers view power outages as a major constraint on firm productivity in developing countries. Yet empirical studies find modest short-run effects of outages on firm performance. This paper builds a dynamic macroeconomic model to study the long-run general-equilibrium effects of power outages on productivity. Outages lower productivity in the model by creating idle resources, depressing the scale of incumbent firms and reducing entry of new firms. Consistent with the empirical literature, the model predicts small short-run effects of eliminating outages. However, the long-run general-equilibrium effects are much larger, supporting the view that eliminating outages is an important development objective.
Keywords: 330